Reduced binding activity of vaccine serum to omicron receptor-binding domain - Li, Mingzhi; Weng, Shiqi; Wang, Quansheng; Yang, Zibing; Wang, Xiaoling; Yin, Yanjun; Zhou, Qiuxiang; Zhang, Lirong; Tao, Feifei; Li, Yihan; Jia, Mengle; Yang, Lingdi; et al. (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) vaccination regimens contribute to limiting the spread of severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2). But the emergence and the rapid transmission of the SARS-CoV-2 variant Omicron raise concerns about the efficacy of the current vaccination strategy. Here, we expressed monomeric and dimeric receptor-binding domains (RBDs) of the spike protein of prototype SARS-CoV-2 and Omicron variant in E.coli and investigated the reactivity of anti-sera from Chinese subjects immunized with SARS-CoV-2 vaccines to these recombinant proteins. In 106 human blood samples collected from 91 participants from Jiangxi, China, 26 sera were identified to be positive for SARS-CoV-2 spike protein antibodies by Lateral Flow Dipstick (LFD) assays, which were enriched in the ones collected from day 7 to 1-month post-boost (87.0%) compared to those harvested within one week post-boost (23.8%) (P<0.0001). A higher positive ratio was observed in the children group (40.8%) than adults (13.6%) (P=0.0073). ELISA results showed that the binding specificity of anti-SARS-CoV-2 antibody-positive sera to Omicron RBDs dropped by 1.48 to 2.07-fold compared to its homogeneous recombinant RBDs. Thus, our data indicate that current SARS-CoV-2 vaccines provide restricted humoral protection against the Omicron variant.